Consumers behaviour towards carbon footprint labels on food: A review of the literature and discussion of industry implications. (10th June 2021) - Rondoni, Agnese; Grasso, Simona
Abstract: Carbon footprint labels allow manufactures to show information about the impact that their food production has on the environment, as well as to help consumers make more sustainable choices. Thus, investigating consumers' reaction towards carbon footprint labels is vital to understand their effectiveness. The aim of this manuscript is to identify the state of the art and research gaps on this topic, by conducting a literature review of published scientific article between 2011 and 2020. In total, 38 papers emerged. Findings show that females, adults, with higher income and educational level have a more positive attitude towards carbon footprint labels. Furthermore, people expressing higher environmental concern and those who are used to buy eco-friendly labelled foods are willing to pay more for carbon footprint labelled foods. However, it also emerges that consumers still have poor knowledge of carbon measurements and the existing carbon footprint label system is still unclear. When carbon footprint labels are re-designed using consumers friendly symbols (e.g., traffic light colours), consumers' understanding significantly increases. Consumers from countries like Egypt and China also show a positive attitude towards carbon footprint information, meaning that a carbon footprint label system should be developed also in the emerging countries. Nonetheless, when carbon footprint is presented with other labels (e.g., organic, Fair Trade etc.) consumers show the lowest willingness to pay for carbon footprint information. It was also found that using a carbon footprint label on environmentally sustainable produced foods (e.g., using upcycled ingredients) increses willingness to pay. Food manufacturers should better inform consumers on carbon footprint labels and policy makers are advised to develop a consumers friendlier carbon footprint label system to incentivize more sustainable choices. This paper is the first to summarize existing literature on consumers' behaviour for carbon footprint labelled foods, providing a discussion of the implications for food manufacturers and policy makers, as well as future research avenues. Highlights: 38 research articles on consumer behaviour for carbon footprint labelled foods were investigated. Concern towards environmental conditions influence consumers attitude for carbon footprint labels. Lack of knowledge towards carbon footprint label system emerged. There is need to develop a commonly recognized footprint label to better drive sustainable choices. Industry implications and future research avenues are discussed.